High-Dose Dependence and Cognitive Side Effects to Medical Prescription of Etizolam - Tamburin, Stefano; Mantovani, Elisa; Bertoldi, Anna; Federico, Angela; Casari, Rebecca; Lugoboni, Fabio (Frontiers in Psychiatry, 2020)
Introduction: The use of novel designer drugs has increased worldwide over the years. Etizolam is a designer benzodiazepine (BZD) that has raised concern because of its growing non-medical use, liability to tolerance and dependence, and related harms. Studies exploring the abuse liability and cognitive effects of etizolam outside the therapeutic doses are lacking. Aims: To explore the abuse liability of etizolam and the characteristics of patients affected by etizolam high-dose dependence in a nationwide tertiary referral addiction unit. To document the cognitive changes to etizolam high-dose use. Design and Methods: Sociodemographic and clinical data on subjects with etizolam high-dose use were retrospectively collected from a database of 1,293 patients consecutively admitted to the Addiction Medicine Unit, Verona University Hospital, Italy for detoxification from high-dose BZDs or Z-drugs dependence. Thorough neuropsychological testing explored the cognitive side effects of high-dose etizolam use. Results: We found eleven etizolam high-dose users, of which eight used etizolam only, and three used etizolam with other BZDs/zolpidem. All the patients were prescribed etizolam for medical reasons, i.e., anxiety and/or insomnia. Neuropsychological evaluation showed deficits of working memory, visuospatial memory and executive function in a 27-year-old woman who used etizolam 15 mg daily. Discussion: Our findings suggest that abuse and dependence liability of etizolam should be considered a public health and social problem. They offer preliminary evidence on the cognitive side effects of etizolam high-dose use. Conclusions: This report offers new information on the potential harms of etizolam in patients who are prescribed this drug for medical reasons.